Coke manufacturing method

By semi-carbonizing the wood biomass and mixing with coal, combined with hot press granulation and dry distillation, the problems of insufficient strength of biomass coke and complex and high cost of production are solved, and the low-cost production of high-strength biomass coke is achieved.

JP7653394B2Active Publication Date: 2025-03-28JFE STEEL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022129088
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-08-12
Publication Date
2025-03-28
Estimated Expiration
2042-08-12

AI Technical Summary

Technical Problem

During the blast furnace process, the strength of the existing biomass coke is insufficient, making it difficult to replace the traditional carbocoke, and the production process is complex and the cost is high.

Method used

By semi-carbonizing the wood biomass, semi-carbides are generated, mixed with coal and crushed into particles of 300 μm or less. After hot pressing granulation and dry distillation, high-strength biomass coke is produced.

Benefits of technology

The production of biomass cokes with sufficient strength for traditional blast furnaces is achieved, while reducing production costs and simplifying the process flow.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653394000002
    Figure 0007653394000002
  • Figure 0007653394000003
    Figure 0007653394000003
  • Figure 0007653394000004
    Figure 0007653394000004
Patent Text Reader

Abstract

To provide a method for producing low-cost, biomass-derived coke that has strength sufficient for use in conventional blast furnace processes.SOLUTION: A method for producing coke includes a semi-carbonization step for heating lignocellulosic biomass to a temperature of 220°C or higher and 330°C or lower in an atmosphere with oxygen supply cut off, to obtain a semi-carbonized material, a mixing step for mixing the semi-carbonized material with coal to obtain a mixture, a pulverization step for pulverizing the mixture to a particle size of 300 μm or smaller, to obtain mixed powder, a molding step for pressurizing the mixed powder to 100 MPa or higher and 300 MPa or lower while being heated to a temperature of 125°C or higher and 300°C or lower, thereby molding the mixed powder to obtain a molding, and a carbonization step for dry-distilling the molding to convert it into coke.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing coke. [Background technology]

[0002] As a measure against global warming, the ironmaking process is also required to balance the amount of greenhouse gas emissions and absorption (so-called carbon neutrality). Since the blast furnace process in ironmaking consumes a large amount of coke and emits carbon dioxide, it is required to reduce the amount of coke derived from fossil fuels used in the blast furnace process, for example.

[0003] Patent Document 1 discloses a method for producing coke using woody biomass. In this production method, biomass is crushed in advance to about 10 mm or less in a crusher. The crushed biomass is transported to a solvent extraction tank, where low molecular components contained in the biomass are extracted using a solvent such as ethanol. The biomass is then heated to 150 to 350°C in a heater and pressure molded in a molding machine to produce a biomass molded product. The biomass molded product is then carbonized and carbonized in a carbonization furnace to produce coke.

[0004] Patent Document 2 describes a composite solid fuel and a method for producing the composite solid fuel. The composite solid fuel contains coal powder and biomass powder. As an example of the method for producing the composite solid fuel, a production method is disclosed that includes a step of heating biomass at 250°C to 500°C, a step of crushing the heated biomass to obtain biomass powder, a step of mixing the biomass powder and the coal powder, and a step of compression molding the mixture obtained in the mixing step at 50 MPa to 150 MPa.

[0005] Non-Patent Document 1 discloses the results of a study on coke strength (strength of molded coke for blast furnaces) using an indirect tensile strength test method. According to this disclosure, it is found that the strength of commercial coke generally used in the blast furnace process is about 3 to 5 MPa in terms of indirect tensile strength. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2004-359898 A [Patent Document 2] Patent Publication No. 2021-176938 [Non-patent literature]

[0007] [Non-Patent Document 1] Study on Coke Strength by Indirect Tensile Strength Test Method (I), Journal of the Fuel Association, Vol. 54, No. 584, 1975, pp. 983-993, A. Miyakawa et al., [Retrieved June 13, 2022], Internet<https: / / www.jstage.jst.go.jp / article / jie1922 / 54 / 12 / 54_12_983 / _pdf> Summary of the Invention [Problem to be solved by the invention]

[0008] However, the blast furnace process is a core technology in pig iron making. Therefore, in the blast furnace process, it is not easy to simply replace fossil fuel-derived coke with biomass-derived coke. For example, it is assumed that pig iron making following the conventional blast furnace process will be difficult unless the coke has a strength equal to or greater than that of commercial coke commonly used in the conventional blast furnace process. In detail, to produce pig iron in a blast furnace, iron ore and coke are alternately charged into the blast furnace and packed in layers, and this packed layer is heated with high-temperature hot air blown in from the tuyeres, and the iron ore is reduced and melted mainly with CO gas generated from the coke. In order to operate such a blast furnace stably, it is necessary to ensure the breathability and liquid permeability of the packed layer in the furnace. For example, if the strength of the coke is low, the coke cannot maintain its shape in the packed layer, and the breathability and liquid permeability of the packed layer may be impaired. Therefore, it is necessary to use coke with a predetermined strength to ensure the breathability and liquid permeability of the packed layer. From an economic point of view, the large increase in the manufacturing cost compared to commercial coke generally used in conventional blast furnace processes is unacceptable, and therefore it is desirable to provide a method for manufacturing biomass-derived coke at low cost and with sufficient strength for use in conventional blast furnace processes.

[0009] The present invention has been made in consideration of the above-mentioned circumstances, and its object is to provide a method for producing biomass-derived coke that has a strength sufficient for use in conventional blast furnace processes and is low-cost. [Means for solving the problem]

[0010] In order to achieve the above object, the present invention provides a method for producing coke, a semi-carbonization step of heating woody biomass to 220°C or higher and 330°C or lower in an atmosphere where oxygen supply is blocked to obtain semi-carbonized material; a mixing step of mixing the torrefied material and coal to obtain a mixture; A grinding step of grinding the mixture to a particle size of 300 μm or less to obtain a mixed powder; a molding step of heating the mixed powder to a temperature in the range of 125° C. to 300° C. and pressurizing the mixed powder to a pressure of 100 MPa to 300 MPa to obtain a molded product; and a carbonization step of converting the briquettes into coke by carbonization.

[0011] In order to achieve the above object, the present invention provides a method for producing coke, a semi-carbonization step of heating woody biomass to 220°C or higher and 330°C or lower in an atmosphere where oxygen supply is blocked to obtain semi-carbonized material; A semi-carbide crushing step of crushing the semi-carbide to a particle size of 300 μm or less to obtain semi-carbide powder; a powder mixing step of mixing the semi-carbide powder with coal powder having a particle size of 300 μm or less to obtain a mixed powder; a molding step of heating the mixed powder to a temperature in the range of 125° C. to 300° C. and pressurizing the mixed powder to a pressure of 100 MPa to 300 MPa to obtain a molded product; and a carbonization step of converting the briquettes into coke by carbonization.

[0012] In order to achieve the above object, the present invention provides a method for producing coke, a semi-carbonization step of heating woody biomass to 220°C or higher and 330°C or lower in an atmosphere where oxygen supply is blocked to obtain semi-carbonized material; A semi-carbide crushing step of crushing the semi-carbide to a particle size of 300 μm or less to obtain semi-carbide powder; a molding step of heating the semi-carbide powder to a temperature in the range of 125° C. to 300° C. and pressurizing the semi-carbide powder to a pressure of 100 MPa to 300 MPa to obtain a molded product; and a carbonization step of converting the briquettes into coke by carbonization. Effect of the Invention

[0013] It is possible to provide a method for producing biomass-derived coke that has a strength sufficient for use in conventional blast furnace processes and is low-cost. [Brief description of the drawings]

[0014] [Figure 1] This is the particle size distribution of powder made by crushing cedar biomass and its semi-carbonized material. [Diagram 2] 1 is a graph showing the components of semi-carbide. [Diagram 3] 1 is a graph showing the relationship between the strength of each molded product in Example 1 and the semi-carbonization treatment temperature. [Figure 4] 1 is a graph showing the relationship between the strength of the coke of Example 1 and the semi-carbonization temperature. [Diagram 5] 1 is a graph showing the relationship between the strength of the coke of Example 1 and the molding temperature. [Figure 6] 1 is a graph showing the relationship between the strength of the coke of Example 1 and the carbonization temperature. [Figure 7] 1 is a SEM photograph of a fracture surface of the coke of Example 1 (when the semi-carbonization temperature was 225° C.). [Figure 8] 1 is a SEM photograph of a fracture surface of the coke of Example 1 (when the semi-carbonization temperature was 250° C.). [Figure 9] 1 is a SEM photograph of a fracture surface of the coke of Example 1 (when the semi-carbonization temperature was 275° C.). [Figure 10] 1 is a SEM photograph of a fracture surface of the coke of Example 1 (when the semi-carbonization temperature was 300° C.). [Figure 11] 1 is a graph showing the relationship between the strength and the blending ratio of the coke of Example 2 (semi-carbonization temperature: 250° C., blended with coal A). [Figure 12] 1 is a graph showing the relationship between the strength and the blending ratio of the coke of Example 2 (semi-carbonization temperature: 275° C., blended with coal A). [Figure 13] 1 is a graph showing the relationship between the strength and the blending ratio of the coke of Example 2 (semi-carbonization temperature: 300° C., blended with coal A). [Figure 14] 1 is a graph showing the relationship between the strength and the blending ratio of the coke of Example 2 (semi-carbonization temperature: 250° C., blended with coal B). [Figure 15]1 is a graph showing the relationship between the strength and the blending ratio of the coke of Example 2 (the semi-carbonization temperature was 275° C., and coal B was blended). [Figure 16] 1 is a graph showing the relationship between the strength and the blending ratio of the coke of Example 2 (semi-carbonization temperature: 300° C., blended with coal B). [Figure 17] 1 is a graph showing the relationship between the strength and the blending ratio of the coke of Example 3 (semi-carbonization temperature: 250° C., blended with coal A). [Figure 18] 1 is a graph showing the relationship between the strength and the blending ratio of the coke of Example 3 (the semi-carbonization temperature was 275° C. and the coal A was blended). [Figure 19] 1 is a graph showing the relationship between the strength and the blending ratio of the coke of Example 3 (semi-carbonization temperature: 300° C., blended with coal A). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] A coke production method according to an embodiment of the present invention will be described with reference to the drawings.

[0016] First embodiment In the coke production method according to this embodiment (hereinafter, sometimes simply referred to as the production method according to this embodiment), coke is produced using woody biomass and coal as raw materials.

[0017] First, an outline of the manufacturing method according to the present embodiment will be described. The manufacturing method according to the present embodiment includes a semi-carbonization step of heating woody biomass to 220°C to 330°C in an atmosphere where the supply of oxygen is blocked to obtain a semi-carbonized material, a mixing step of mixing the semi-carbonized material with coal to obtain a mixture, a crushing step of crushing the mixture to a particle size of 300 μm or less to obtain a mixed powder, a molding step of molding the mixed powder by pressurizing it to 100 MPa to 300 MPa in a state where the mixture is heated to a temperature in the range of 125°C to 300°C to obtain a molded product, and a carbonization step of carbonizing the molded product to convert it into coke.

[0018] The manufacturing method according to the present embodiment can provide a method for manufacturing biomass-derived coke at low cost and with sufficient strength for use in a conventional blast furnace process. The manufacturing method according to the present embodiment will be described in detail below.

[0019] The strength of the coke in this embodiment refers to the indirect tensile strength in cold measured by the method described in Non-Patent Document 1. Hereinafter, the strength measured by this method will be simply referred to as strength. In the following explanation, coke having a strength that can be used in a conventional blast furnace process may be referred to as high-strength coke. In addition, when coke has a strength that can be used in a conventional blast furnace process, it may be described that the strength of the coke is high. In this embodiment, the coke having a strength that can be generally used in a blast furnace process refers to a high-strength coke with a tensile strength of 3 MPa or more.

[0020] The semi-carbonization step is a step of semi-carbonizing woody biomass to obtain semi-carbonized woody biomass. Hereinafter, the semi-carbonized woody biomass will be simply referred to as semi-carbonized woody biomass. Semi-carbonization is a process of pyrolyzing organic resources derived from plants and animals, such as woody biomass, at a predetermined temperature (in this embodiment, 220°C or higher and 330°C or lower) to produce a solid material with a large amount of carbon components and a large amount of heat per unit mass, i.e., semi-carbonized woody biomass. Semi-carbonization may also be referred to as roasting or torrefaction. Hereinafter, semi-carbonizing woody biomass will be referred to as semi-carbonization processing. Note that semi-carbonization processing does not require a large processing cost and is inexpensive.

[0021] By semi-carbonizing woody biomass, not only can the amount of heat be increased as described above, but also the crushability in the crushing process and the moldability in the molding process can be improved. Details will be described later.

[0022] Woody biomass is a resource made of wood such as conifers, such as cedar, pine, and cypress, and broad-leaved trees, such as zelkova and birch, and the parts of the wood are not limited. Woody biomass also includes unused parts such as waste wood and forest residues after use for building materials and papermaking. A specific example of woody biomass is sawdust.

[0023] The size of the woody biomass when semi-carbonized is not particularly limited, and it may be of a size that is easy to handle, for example, does not cause problems during semi-carbonization. The woody biomass may be crushed as necessary. As an example, the woody biomass may be crushed to a size of 50 mm or less. The woody biomass may be of a size similar to sawdust (for example, 3 mm or less). The size of the woody biomass may be evaluated by visual inspection and measurement with a ruler, or measurement with a sieve.

[0024] It is preferable that the woody biomass is dried in advance (pre-dried). This makes it possible to reduce the processing time and energy consumption in the subsequent semi-carbonization step. The moisture content of the woody biomass is preferably 30 (wt%db) or less on a dry basis, and more preferably 15 (wt%db) or less. Hereinafter, the woody biomass may be simply referred to as biomass.

[0025] The semi-carbonization process is carried out in an atmosphere where the supply of oxygen is blocked, for example, by storing the biomass in a container that forms a space where the inflow of air is prevented and an inert gas flows through. The semi-carbonization process can be carried out by heating the container that stores the biomass and heating the biomass to 220°C or higher and 330°C or lower by heat transfer from the container. Hereinafter, the heating temperature in the semi-carbonization process is simply referred to as the semi-carbonization process temperature.

[0026] From the viewpoint of producing coke with higher strength, the semi-carbonization temperature is preferably 250°C or more and 300°C or less. Usually, the reaction rate of the pyrolysis reaction in the semi-carbonization process is fast, so the time required for the reaction to be completed is short. Therefore, the treatment time required for the semi-carbonization process is 1 minute or more. The semi-carbonization process time is preferably 10 minutes or more. This eliminates the temperature difference between the biomass and the container, and the entire biomass can be semi-carbonized uniformly. In addition, the temperature of the entire biomass can be reliably raised to the semi-carbonization process temperature evenly (i.e., heated evenly) to perform the semi-carbonization process, and the quality variation of the semi-carbonized product can be suppressed. There is no particular upper limit for the semi-carbonization process time, but if the treatment time is too long, the required energy increases and the cost increases, which is not preferable, and 60 minutes or less is preferable. The semi-carbonization process time refers to the time during which the semi-carbonization process temperature is maintained from the time when the predetermined semi-carbonization process temperature is reached.

[0027] The semi-carbonization treatment can be carried out using a heating device such as an electric furnace, a rotary kiln, a fluidized bed heating furnace, a screw type heating furnace, a shaft furnace, or a carbonization furnace.

[0028] The mixing step is a step of mixing the torrefied material and the coal to obtain a mixture. Hereinafter, the mixture of the torrefied material and the coal will be simply referred to as a mixture.

[0029] The type of coal is not limited, but the coal used in this embodiment is subbituminous coal, bituminous coal, and semi-anthracite, each of which has a weight-based percentage (wt%daf) of the elemental composition of carbon according to elemental analysis of 70% to 95%. The particle size of the coal may be any size that does not interfere with the subsequent mixing process. The coal may be crushed as necessary. The particle size of the coal may be, for example, 3 mm or less. It is preferable that the particle size of the coal is close to the particle size of the semi-carbide. This makes it easy to mix the semi-carbide and the coal. The ratio of the particle size of the coal to the particle size of the semi-carbide is preferably 75% to 150%.

[0030] The blending ratio of the semi-carbide and the coal (mixing ratio, hereinafter sometimes simply referred to as ratio) may be changed according to the required properties of the coke to be produced, such as the calorific value, the amount of carbon, the specific gravity, or the desired strength. For example, if it is desired to increase the carbon content of the coke, it is preferable to increase the proportion of coal. From the viewpoint of carbon neutrality, it is preferable to increase the amount of carbon derived from biomass in the coke, and therefore it is preferable to increase the proportion of semi-carbide. The blending ratio of semi-carbide in the mixture is preferably 1 mass% or more, more preferably 5 mass% or more, and even more preferably 40 mass% or more.

[0031] The method and device for mixing the semi-carbide and the coal are not particularly limited. It is preferable that the mixture is mixed uniformly to a certain extent. This may improve the strength of the molded product and coke described later. In this embodiment, since the pulverization step is performed after the mixing step, the uniformity of the mixture in the mixing step may be such that handling in the pulverization step is not hindered.

[0032] The method and device for mixing the semi-carbide and the coal may be to mix them with a shovel or a crane bucket while they are piled up in a storage area, or to drop the semi-carbide and the coal onto a belt conveyer from a hopper equipped with a fixed amount of feed device such as a blending tank. Also, a mixer for powders may be used to improve the uniformity of the mixture.

[0033] The pulverization step is a step of pulverizing the mixture into a powder having a particle size of 300 μm or less. Hereinafter, the pulverized powder of the mixture is simply referred to as a mixed powder. The mixed powder is a mixed powder of semi-carbide powder obtained by pulverizing semi-carbide and coal powder obtained by pulverizing coal.

[0034] In the manufacturing method according to the present embodiment, as described above, the particle diameter of the mixed powder is 300 μm or less. In addition, the particle diameter in this application means the maximum particle diameter unless otherwise specified. When measuring with a particle size distribution measuring device, the maximum particle diameter can be measured as follows.

[0035] The particle size and particle size distribution of the mixed powder may be values ​​measured using a commercially available particle size distribution measuring device. In this embodiment, an image type particle size distribution measuring device "Morphologi 4" (hereinafter simply referred to as particle size distribution measuring device) manufactured by Malvern Panalytical is used, images of 55,000 to 74,000 particles are obtained with a microscope built into the device, and particle size and particle size distribution based on the circle equivalent particle size (projected area circle equivalent diameter) obtained by image analysis using software attached to the device are used. That is, the particle size of the particles contained in the mixed powder measured by the particle size distribution measuring device, which is 95% of the particles when accumulated from the smallest particles, is defined as the maximum particle size (maximum value). In this application, unless otherwise specified, the particle size refers to the maximum particle size. Hereinafter, when simply referring to particle size or particle size distribution, it means the value measured by the above particle size distribution measuring device. In addition, the particle size of the particles which is 95% of the particles when accumulated from the largest particles is defined as the minimum particle size (minimum value). In addition, when the minimum particle diameter and the maximum particle diameter in the particle size distribution are indicated, this is sometimes referred to as the width of the particle size distribution and is indicated as "(minimum value) to (maximum value)." In addition, when the particle diameter and particle size distribution of a powder other than the mixed powder in the explanation of the production method according to the present embodiment are explained, the same terms, usages, examples, or meanings are used as in the case of the above-mentioned mixture.

[0036] If the mixed powder contains coarse particles having a particle size exceeding 300 μm, the coarse particles may remain in the molded product or coke and reduce the strength of the molded product or coke because defects are likely to form around the coarse particles in the molded product or coke.

[0037] In the manufacturing method according to the present embodiment, the particle size of the mixed powder is preferably 100 μm or less. When the particle size of the mixed powder is appropriately small, the physical structure in the molded product or coke becomes dense and uniform, which contributes to increasing the strength of the coke. In addition, when appropriate molding is performed, the finer the particle size of the mixed powder, the stronger the molded product or coke is, which is preferable. Therefore, the minimum particle size of the mixed powder is not limited. However, if the particle size is made too small, molding becomes difficult, and the bulk density of the molded product decreases, which may actually decrease the strength of the coke. In addition, considering productivity, even if the particle size of the mixed powder is made small, making the maximum particle size of the particles contained in the mixed powder less than 20 μm increases the molding cost, but there is no improvement in performance after molding, and there is a possibility that a problem of molding becomes difficult. For this reason, if the maximum particle size is 20 μm or more, coke with sufficient strength for use in the conventional blast furnace process can be manufactured. The minimum particle size of the mixed powder is not particularly limited.

[0038] The method or device for pulverizing the mixture is not particularly limited. As a device for pulverizing the mixture, a media mill such as a cutter mill, a hammer mill, a pin mill, a jet mill, or a ball mill may be used. The pulverizing device is not limited to a device that performs only pulverization, and for example, a pulverizer with a built-in classifier may be used.

[0039] In this embodiment, since the woody biomass in the mixture is semi-carbonized, the crushability is improved compared to the case where a mixture of woody biomass and coal is crushed. Note that, "improved crushability" means that a larger amount of the mixture can be crushed with the same crushing energy, or the particle size of the mixed powder crushed with the same crushing energy is smaller. In other words, by semi-carbonizing the woody biomass, the crushability can be improved and the cost can be reduced.

[0040] FIG. 1 shows a reference example of the particle size distribution (volume basis) of powders when cedar biomass and semi-carbonized cedar biomass are crushed under the same crushing conditions. The semi-carbonized cedar biomass is shown when the semi-carbonization temperature is changed from 225°C to 325°C. As shown in FIG. 1, the semi-carbonized cedar biomass is crushed more finely than the cedar biomass. Also, in the semi-carbonized cedar biomass, the higher the semi-carbonization temperature is, the more finely the semi-carbonized cedar is crushed. In this way, semi-carbonization can improve crushability and reduce costs.

[0041] In principle, a stirring phenomenon occurs during the pulverization process, so the uniformity of the mixed powder naturally improves by pulverizing the mixture.

[0042] The molding step is a step in which the mixed powder is pressure molded (compression molded) to obtain a molded product. In the molding step, the mixed powder is heated to a temperature in the range of 125°C to 300°C, and then pressurized to 100 MPa to 300 MPa to mold it. The molding of the mixed powder performed in the molding step is so-called hot molding. Hereinafter, the heating temperature of the mixed powder in the molding step is referred to as the molding temperature. Also, the pressure applied to the mixed powder in the molding step is referred to as the molding pressure.

[0043] By heating the mixed powder to the above temperature range, i.e., by setting the molding temperature to the above temperature range, the plasticity of the semi-carbide powder and coal powder particles in the mixed powder is improved. By pressing the mixed powder in a state in which the plasticity of the mixed powder is improved in this way, the semi-carbide powder and coal powder are sufficiently deformed and bonded, making it possible to produce a molded product with high strength. The strength of the molded product produced by the manufacturing method according to this embodiment is evaluated in the same manner as the strength of coke.

[0044] If the molding temperature is less than 125°C, the mixed powder may not be sufficiently plasticized. In this case, it may not be possible to manufacture a high-strength molded product. Conversely, if the molding temperature exceeds 300°C, gas may be generated due to thermal decomposition, which may hinder molding. In addition, carbonization may progress during molding, causing the thermoplasticity to be lost, resulting in a decrease in the strength of the molded product.

[0045] Incidentally, when the strength of the molded product produced by the manufacturing method according to the present embodiment is sufficiently high, the density of the molded product is also sufficiently high. In a molded product with low density, the distance between particles inside is large and the number of contact points between particles is small, resulting in a sparse internal structure, and therefore the strength of the molded product is reduced. In other words, by increasing the density of the molded product, the strength of the molded product can be increased.

[0046] The higher the molding pressure, the higher the density of the molded product, and therefore the strength of the coke after carbonization. If the molding pressure is 100 MPa or more, the effect of improving density or strength becomes saturated. This makes the quality of the molded product (density and strength) stable. Therefore, the molding pressure should be 100 MPa or more. If the molding pressure is less than 100 MPa, it may not be possible to obtain a high-strength molded product.

[0047] However, if the molding pressure exceeds 300 MPa, the residual stress after molding will be large, and molding defects such as rebound cracks may occur in the molded product. This may result in a decrease in the strength of the molded product. Therefore, the molding pressure is set to 300 MPa or less.

[0048] The method or apparatus for pressurizing the mixed powder is not particularly limited. The pressurization of the mixed powder may be mechanical compression, that is, the mixed powder may be accommodated in a space surrounded by a wall such as a mold or a compression roll, and pressurized by compression through the wall. As the pressurization apparatus, a pelletizer, a double roll molding machine, an extrusion molding machine, etc. can be used. To explain using a double roll molding machine as an example, pressurization (compression) molding can be performed in the die cavity of the compression roll by the mechanical action of the roll.

[0049] In the molding step, the mixed powder is heated to the above-mentioned molding temperature and then pressed to mold. In order to obtain a more suitable molded product, it is desirable to heat the powder-contacting parts of the molding machine (the wall parts that form the space for accommodating the mixed powder and molding it, the compression rolls in the case of a double-roll molding machine or extrusion molding machine) and maintain the temperature of the raw materials at the above-mentioned molding temperature. This makes it possible to avoid molding defects.

[0050] The carbonization step is a step in which the briquettes are carbonized by dry distillation and converted into coke.

[0051] The carbonization of the molded product is carried out in an atmosphere in which the supply of oxygen is blocked. For example, the carbonization of the molded product may be carried out in a space in which the inflow of air is blocked and an inert gas is passed through.

[0052] The carbonization of the molded product may be carried out by heating the molded product to a temperature of 500° C. to 1250° C. The temperature reached when the molded product is carbonized is hereinafter referred to as the carbonization temperature.

[0053] By setting the carbonization temperature at 500°C or higher, it is possible to produce coke with high strength. The carbonization temperature is preferably set to 900°C or higher and 1250°C or lower. The carbonization temperature is preferably set to 900°C or higher and 1100°C or lower. This allows the production of coke with even higher strength.

[0054] From the viewpoint of reducing energy consumption during carbonization and lowering costs, the carbonization temperature may be set to 500° C. or higher and 900° C. or lower, preferably 500° C. or higher and 800° C. or lower. This makes it possible to produce high-strength coke and reduce costs.

[0055] If the carbonization temperature exceeds 1250°C, the briquettes may lose hetero elements, resulting in a decrease in the strength of the coke.

[0056] The heating rate until the carbonization temperature is reached is preferably 30° C. / min or less. By setting the heating rate at 30° C. / min or less, it is possible to avoid a decrease in the strength of the coke.

[0057] Carbonization can be performed using, for example, a coke oven having a combination of a combustion chamber and a carbonization chamber, a rotary kiln, an electric furnace, a shaft furnace, a carbonization furnace, etc. In the case of a coke oven, the molded material contained in the carbonization chamber is carbonized to produce coke by controlling the heating rate to 30°C / min or less according to a predetermined heating schedule and controlling the temperature to reach a carbonization temperature of 500°C or more and 1250°C or less before the end of the carbonization.

[0058] In this manner, it is possible to provide a method for producing biomass-derived coke that has sufficient strength for use in conventional blast furnace processes and is low cost.

[0059] Second Embodiment The second embodiment differs from the first embodiment in that, instead of obtaining a mixture and then pulverizing it to obtain a mixed powder as in the first embodiment, semi-carbide is pulverized to obtain semi-carbide powder, which is then mixed with coal powder to obtain a mixed powder, but otherwise is generally the same as the first embodiment. The following description will focus on the differences from the first embodiment, and descriptions of common parts will be omitted as appropriate. Hereinafter, the coke manufacturing method according to the second embodiment may simply be referred to as the manufacturing method according to the present embodiment.

[0060] First, an outline of the manufacturing method according to the present embodiment will be described. The manufacturing method according to the present embodiment includes a semi-carbonization step of heating woody biomass at 220°C to 330°C in an atmosphere where the supply of oxygen is blocked to obtain semi-carbonized material, a semi-carbonized material crushing step of crushing the semi-carbonized material to a particle size of 300 μm or less to obtain semi-carbonized powder, a powder mixing step of mixing the semi-carbonized powder with coal powder having a particle size of 300 μm or less to obtain a mixed powder, a molding step of molding the mixed powder by applying a pressure of 100 MPa to 300 MPa in a state where the mixture is heated to a temperature range of 125°C to 300°C to obtain a molded product, and a carbonization step of carbonizing the molded product to convert it into coke.

[0061] The semi-carbonization step, molding step, and carbonization step in the manufacturing method according to this embodiment are the same as those in the first embodiment.

[0062] The manufacturing method according to the present embodiment can provide a method for manufacturing biomass-derived coke at low cost and with sufficient strength for use in a conventional blast furnace process. The manufacturing method according to the present embodiment will be described in detail below.

[0063] From the viewpoint of producing coke having higher strength, the semi-carbonization temperature is preferably set to 240°C or higher and 310°C or lower.

[0064] The semi-carbide crushing step is a step of crushing the semi-carbide into a powder having a particle size of 300 μm or less, preferably 100 μm or less. Hereinafter, the crushed semi-carbide powder is simply referred to as semi-carbide powder. The semi-carbide crushing step is performed to make the particle size of the mixed powder 300 μm or less. The mixed powder is the same as in the first embodiment. In addition, various requirements and aspects related to the particle size of the semi-carbide powder, and the crushing method and device are the same as those described in the first embodiment.

[0065] The powder mixing step is a step of mixing semi-carbide powder with coal powder having a particle size of 300 μm or less, preferably 100 μm or less, to obtain a mixed powder. The reason why coal powder having a particle size of 300 μm or less is used is to make the particle size of the mixed powder 300 μm or less as described above.

[0066] The coal powder may be obtained by crushing coal. The coal powder may be a purchased product, or may be produced by a coal crushing step in which coal is crushed to a particle size of 300 μm or less to obtain coal powder. Various requirements and aspects related to the particle size of the coal powder, and the crushing method and device are the same as those described in the first embodiment with respect to the various requirements and aspects related to the particle size of the mixed powder.

[0067] The mixing method and mixing device of the semi-carbide powder and the coal powder are not particularly limited as long as they are suitable for mixing powders of 300 μm or less. It is preferable that the mixed powder is uniform in its mixed state. This may improve the strength of the molded product and coke described later. Examples of the mixing method and mixing device of the semi-carbide with coal include those that utilize rotational force and those that utilize shear force. From the viewpoint of obtaining a high mixing capacity in a short time, a mixing device that utilizes shear force is preferable as the mixing method and mixing device of the semi-carbide with coal. Examples of the mixing device that utilizes rotational force include a cone-type mixer equipped with a screw-type agitator that rotates and revolves around its axis, a V-type blender mixer equipped with a rotating agitator blade at the bottom, and a static mixer with multiple twisted baffles arranged in the flow path. Examples of the mixing device that utilizes shear force include an Eirich mixer, an Apex mixer, a Lödige mixer, and the like equipped with a high-speed rotating blade (chopper) that imparts a strong shear rate to the mixture and promotes shear mixing.

[0068] The manufacturing method according to this embodiment may be advantageous compared to the manufacturing method according to the first embodiment when the location or facility where the semi-carbide crushing step or the coal crushing step is performed is different from the location or facility where the powder mixing step is performed.

[0069] In this manner, it is possible to provide a method for producing biomass-derived coke that has sufficient strength for use in conventional blast furnace processes and is low cost.

[0070] Third embodiment The third embodiment differs from the second embodiment in that, instead of obtaining coke from woody biomass and coal as in the second embodiment, coke is produced using only woody biomass as a raw material, does not include a powder mixing step, and in the molding step, semi-carbide powder is molded instead of the mixed powder to obtain a molded product, and in the carbonization step, the molded product formed only from the semi-carbide powder is carbonized to convert it into coke. The rest of the third embodiment is generally the same as the second embodiment. The following description will focus on the differences from the second embodiment, and the description of the common parts with the first and second embodiments will be omitted as appropriate. The method for producing coke according to the third embodiment may hereinafter be simply referred to as the manufacturing method according to this embodiment.

[0071] First, an outline of the manufacturing method according to the present embodiment will be described. The manufacturing method according to the present embodiment includes a semi-carbonization step of heating woody biomass to 220°C to 330°C in an atmosphere where the supply of oxygen is blocked to obtain semi-carbonized material, a semi-carbonized material crushing step of crushing the semi-carbonized material to a particle size of 300 μm or less to obtain semi-carbonized powder, a molding step of molding the semi-carbonized powder by applying a pressure of 100 MPa to 300 MPa in a state where the semi-carbonized material is heated to a temperature in the range of 125°C to 300°C to obtain a molded product, and a carbonization step of carbonizing the molded product to convert it into coke.

[0072] The semi-carbonization step, the semi-carbonized material crushing step, and the carbonization step in the manufacturing method according to this embodiment are the same as those in the second embodiment.

[0073] From the viewpoint of producing coke having higher strength, the semi-carbonization temperature is preferably set to 240°C or higher and 310°C or lower.

[0074] The molding step in the manufacturing method according to this embodiment differs from the molding steps in the first and second embodiments in that only semi-carbide powder is molded to obtain a molded product, but in other respects is similar to the molding steps in the first and second embodiments.

[0075] The carbonization step in the manufacturing method of this embodiment differs from the carbonization steps of the first and second embodiments in that the molded product to be dry distilled is formed only from semi-carbonized powder, but in other respects is similar to the carbonization step of the first and second embodiments.

[0076] In this manner, it is possible to provide a method for producing biomass-derived coke that has sufficient strength for use in conventional blast furnace processes and is low cost. EXAMPLES

[0077] The present embodiment will be described below based on examples, but the present embodiment is not limited to the following examples.

[0078] Example 1 The coke of Example 1 was produced using cedar biomass as woody biomass.

[0079] An electric heating furnace was used as the heating device for the semi-carbonization treatment. An inert gas was circulated inside the furnace to block the supply of oxygen to the furnace. Biomass was charged into the furnace, heated to a predetermined semi-carbonization temperature, and then held at the predetermined semi-carbonization temperature for 60 minutes to obtain semi-carbonized material. The predetermined semi-carbonization temperatures used were 225°C, 250°C, 275°C, 300°C, and 325°C.

[0080] FIG. 2 shows a graph showing the components of semi-carbonized products. In the graph in FIG. 2, the series of legends "untreated" indicates biomass that was not semi-carbonized, and the series of legends "T225" to "T325" in the graph indicate the results of semi-carbonized products with semi-carbonization temperatures of 225°C, 250°C, 275°C, 300°C, and 325°C, respectively. In the graph in FIG. 2, the content is based on the raw material mass (value where the mass of biomass is 1), and the height of the graph bar at each temperature is the yield of semi-carbonized products relative to the raw material (biomass). As shown in FIG. 2, when the semi-carbonization temperature is 300°C or higher, cellulose and hemicellulose (hereinafter collectively referred to as celluloses) are greatly reduced.

[0081] Next, 10 g of the semi-carbide was pulverized to obtain semi-carbide powder. The pulverization process was performed using a cutter mill (manufacturer: Osaka Chemical Co., Ltd., model: WB-1) or a ball mill (manufacturer: Nitto Kagaku Co., Ltd., model: ANZ-61S).

[0082] The pulverization time in the cutter mill was 1 minute. The semi-carbide powder pulverized in the cutter mill had a particle size distribution width of 5 μm to 100 μm. The pulverization time in the ball mill was 10 hours or 20 hours. The semi-carbide powder pulverized in the ball mill for 10 hours had a particle size distribution width of 2 μm to 40 μm. The semi-carbide powder pulverized in the ball mill for 20 hours had a particle size distribution width of 1 μm to 20 μm. The semi-carbide powder pulverized in the cutter mill was used for the pulverization in the ball mill.

[0083] Next, the semi-carbide powder was molded. A uniaxial hot molding machine was used for molding. The inner diameter of the die was about 14 mm. For example, a predetermined amount of semi-carbide powder heated to 200°C was charged into the die, and a pressure of, for example, 128 MPa was applied to the semi-carbide powder charged in the die with a punch to obtain a molded product. That is, for example, a molding temperature of 200°C and a molding pressure of 128 MPa were set to obtain a molded product. During molding, the temperature of the die mold was maintained at a predetermined molding temperature (for example, 200°C). The molded product was a disk-like (cylindrical) shape with a diameter of about 14 mm and a thickness of about 5 mm.

[0084] Fig. 3 shows a graph showing the relationship between the strength (cold indirect tensile strength) and semi-carbonization temperature of each molded product of Example 1 (where the molding pressure of the molded products was 128 MPa and the molding temperature was 200°C). In Fig. 3, "CM" shows a molded product made using semi-carbonized powder pulverized with a cutter mill. "MB10h" and "MB20h" show molded products made using semi-carbonized powder pulverized with a ball mill, with pulverization times of 10 hours and 20 hours, respectively.

[0085] In the graph of Figure 3, almost no temperature dependency is observed in the strength of the molded product when the semi-carbonization temperature is 275°C or lower. When the temperature exceeds 275°C, the strength of the molded product tends to decrease.

[0086] As shown in the graph of FIG. 3, among the molded products of Example 1, those processed at a semi-carbonization temperature of 275°C or less have a strength of 5 to 9 MPa, which is significantly higher than the strength (1 to 4 MPa) of those processed at a semi-carbonization temperature of 300°C or more. The strength of those processed at a semi-carbonization temperature of 300°C is 3 to 3.5 MPa. From the results shown in the graph of FIG. 3, it can be seen that if the semi-carbonization temperature is 220°C or more and 300°C or less, the strength of the molded product is 3 MPa or more. Also, from the results shown in the graph of FIG. 3, it can be seen that if the semi-carbonization temperature is 220°C or more and 280°C or less, the strength of the molded product is 5 MPa or more, which is particularly high strength.

[0087] Although not shown in FIG. 3, the strength of the molded product (hereinafter referred to as the molded product of Comparative Example 1) obtained by molding biomass powder (not subjected to semi-carbonization treatment) pulverized with a cutter mill so that the particle size is 100 μm or less at the same molding temperature and molding pressure as above was 3.2 MPa, and the product subjected to semi-carbonization showed higher strength. As described above, when the semi-carbonization temperature is 300°C, the strength of the molded product decreases, but the strength is equivalent to that of the product not subjected to semi-carbonization treatment (molded product of Comparative Example 1). When the semi-carbonization temperature is 275°C or less, the strength of the molded product is significantly higher than that of the product not subjected to semi-carbonization treatment (molded product of Comparative Example 1).

[0088] Considering the results shown in the graph of Figure 2, it is believed that the amount of cellulose remaining in the semi-carbonized material affects the moldability of the briquettes. In other words, to form a high-strength briquettes, it is sufficient to adopt a semi-carbonization temperature (275°C or lower) at which little cellulose is lost. Also, to produce high-strength coke, it is preferable to adopt a semi-carbonization temperature (275°C or lower) at which little cellulose is lost. This is because if the strength of the briquettes is high, wear and powdering of the briquettes before carbonization is suppressed, and it is expected that the shape and physical properties of the coke produced from the briquettes will be uniform.

[0089] Thus, the semi-carbonization treatment made it possible to obtain a molded product having higher strength than when the semi-carbonization treatment was not performed.

[0090] Next, the above-mentioned shaped product was carbonized by dry distillation to produce coke.

[0091] An electric heating furnace was used for carbonization of the briquettes. The carbonization temperature was 1000°C unless otherwise specified. An inert gas was circulated inside the heating furnace to block the supply of oxygen to the furnace. The above-mentioned briquettes were charged into the heating furnace, and the temperature was raised to 1000°C at a heating rate of 3°C / min unless otherwise specified to produce coke.

[0092] FIG. 4 shows a graph showing the relationship between the strength of the coke of Example 1 and the semi-carbonization temperature (wherein the molding pressure of the molded product was 128 MPa, the molding temperature was 200°C, the carbonization temperature was 1000°C, and the heating rate was 3°C / min). In the graph of FIG. 4, the series with the legend "CM" indicates coke made using cutter mill crushed product. Also, in FIG. 4, the series with the legend "MB10h" and "MB20h" indicate coke made using ball mill crushed product, with crushing times of 10 hours and 20 hours, respectively.

[0093] As shown in the graph in FIG. 4, all of the cokes were high-strength cokes with strengths exceeding 5 MPa.

[0094] As shown in the graph of FIG. 4, the strength of the coke depends on the semi-carbonization process and the particle size or particle size distribution (crushing conditions) of the semi-carbonized powder. The smaller the particle size of the semi-carbonized powder, the higher the strength of the coke. The strength of the coke is highest when the semi-carbonization process temperature is 275°C. The strength of the coke when the semi-carbonization process temperature is 275°C is 17 to 32 MPa.

[0095] The strength of the coke obtained by carbonizing the molded product of Comparative Example 1 in the same manner as described above (hereinafter referred to as the coke of Comparative Example 1) was 4.7 MPa, which was high, but was lower than that of any of the cokes that had been subjected to the semi-carbonization treatment of Example 1.

[0096] Fig. 5 shows a graph showing the relationship between the strength of the coke in Example 1 and the molding temperature. The series of "T225" to "T300" in the legend in the graph in Fig. 5 show the results of cokes using semi-carbonized materials with semi-carbonization temperatures of 225°C, 250°C, 275°C, and 300°C (however, cokes using cutter mill crushed products). The relationship between the molding temperature and the coke strength was evaluated by producing cokes with different molding temperatures for each semi-carbonized material and evaluating the strength of each. The cokes with different molding temperatures were produced using the above-mentioned cutter mill crushed products.

[0097] From Fig. 5, it can be seen that the coke strength improves with increasing molding temperature regardless of the semi-carbonization temperature used as the raw material. The graph also shows that if the molding temperature is 125°C or higher, the coke has the necessary strength.

[0098] FIG. 6 shows a graph showing the relationship between the strength of the coke in Example 1 and the carbonization temperature. The series of "T225" to "T300" in the legend in the graph in FIG. 6 show the results of cokes using semi-carbonized materials with semi-carbonization temperatures of 225°C, 250°C, 275°C, and 300°C, respectively (however, cokes using cutter mill crushed products). The relationship between the carbonization temperature and the strength of the coke was evaluated by producing cokes with different carbonization temperatures for each semi-carbonized material and evaluating the strength of each. The cokes with different carbonization temperatures were produced by heating the molded products using the above-mentioned cutter mill crushed products to the respective carbonization temperatures at a heating rate of 3°C / min.

[0099] The graph in Figure 6 reveals the following. In all cases where the semi-carbonization temperature is 225°C, 250°C, 275°C, or 300°C, the strength of the coke exceeds 4 MPa when the carbonization temperature is 300°C or higher. In all cases where the semi-carbonization temperature is 225°C, 250°C, 275°C, or 300°C, coke with a strength exceeding 5 MPa can be obtained if the carbonization temperature is 500°C or higher. In all cases where the semi-carbonization temperature is 225°C, 250°C, 275°C, or 300°C, the strength of the coke with a carbonization temperature of 400°C or higher and 500°C or lower is approximately 5 MPa.

[0100] The graph shown in FIG. 6 also shows the following. When the carbonization temperature is 500° C. or more and 1000° C. or less, the semi-carbonization temperature affects the strength of the coke. When the carbonization temperature is 500° C. or more and 1000° C. or less, the strength of the coke is highest when the carbonization temperature is 275° C. In addition, the graph shown in FIG. 6 also shows the following. The increase in the strength of the coke starts at 500° C. or more, and increases monotonically until the carbonization temperature reaches 1000° C., and the higher the carbonization temperature, the higher the strength achieved. Considering this, at least the carbonization temperature normally used can be applied in this embodiment. Although the upper limit is not particularly set, it is preferable that the carbonization temperature is 1250° C. or less, which is known to cause detachment of hetero elements in the molded product and to reduce the strength of the coke.

[0101] In addition, in the graph shown in FIG. 6, as described above, the strength of the coke increases monotonically until the carbonization temperature reaches 1000°C. In consideration of this, it is considered that the upper limit of the appropriate carbonization temperature is at least 1100°C, and that even at 1250°C, adequate carbonization can be performed and high-strength coke can be produced. That is, from the graph shown in FIG. 6, it can be said that high-strength coke can be produced by setting the carbonization temperature to 500°C or higher and 1250°C or lower. Furthermore, from the graph in FIG. 6, it can be said that, in particular, coke with even higher strength can be produced by setting the carbonization temperature to 900°C or higher and 1100°C or lower.

[0102] From the viewpoint of reducing energy consumption during carbonization and lowering costs, it can be seen from the graph shown in Fig. 6 that the carbonization temperature may be set to 500°C or higher and 900°C or lower, preferably 500°C or higher and 800°C or lower. Even with a carbonization temperature in this range, coke with sufficiently high strength can be produced. That is, by setting the carbonization temperature to 500°C or higher and 900°C or lower, preferably 500°C or higher and 800°C or lower, it is possible to produce high-strength coke and reduce costs.

[0103] 7 to 10 show electron microscope enlarged photographs (SEM photographs) of the fracture surfaces of coke (coke made by using cutter mill crushed material and carbonizing at 1000°C). Figures 7 to 10 show the fracture surfaces of coke when the semi-carbonization temperatures were 225°C, 250°C, 275°C, and 300°C, respectively.

[0104] When the semi-carbonization temperature was low (225℃ and 250℃), a compressed honeycomb structure derived from the tracheids, the biological tissue structure of the cedar used as biomass, remained. It is believed that the honeycomb structure softened due to the heat applied during molding, and was deformed and compressed due to the pressure applied during molding, but the structure was not destroyed.

[0105] On the other hand, when the semi-carbonization temperature is high (275°C and 300°C), the honeycomb structure is destroyed. It is considered that the softening or thermoplasticity due to heating during molding is reduced or impaired by the semi-carbonization, and the structure is destroyed by the pressure during molding. When the semi-carbonization temperature is high (275°C and 300°C), a plate stacking structure (a structure in which the walls of the destroyed honeycomb structure are stacked to form plate-shaped particles) is generated after the honeycomb structure is destroyed, and this stacking structure creates new bonding points between the plate-shaped particles during carbonization, so that the strength of the coke increases significantly at temperatures between 500°C and 1000°C (the so-called breakdown / build-up effect), as shown in the graph in Figure 6.

[0106] If the semi-carbonization temperature is too high (325°C or higher), the individual plate-shaped particles lose their thermoplasticity excessively, and as a result, it is believed that the plate-shaped particles are unable to form a structure that facilitates bonding during carbonization. As a result, as shown in the graph in Figure 4, if the semi-carbonization temperature is too high (325°C or higher), the strength of the coke is thought to decrease.

[0107] Example 2 The same cedar biomass as in Example 1 was used as woody biomass, which was converted into semi-carbonized powder and further mixed (blended) with coal to produce coke in Example 2. Example 2 differs from Example 1 in that coal was further used as a raw material for the coke. In Example 2, coke was produced under a molding pressure of 128 MPa, a molding temperature of 200°C, a carbonization temperature of 1000°C, and a heating rate of 3°C / min. In the following explanation, explanations of parts similar to those in Example 1 may be omitted.

[0108] Biomass was charged into the heating furnace, heated to a prescribed semi-carbonization temperature, and then held at the prescribed semi-carbonization temperature for 60 minutes to obtain semi-carbonized material. The prescribed semi-carbonization temperatures were 250°C, 275°C, and 300°C.

[0109] The semi-carbide was pulverized by a cutter mill in the same manner as in Example 1 to obtain semi-carbide powder having a particle size distribution range of 5 μm to 100 μm.

[0110] As coal, a first coal (coal A) and a second coal (coal B) different from the first coal were prepared. The following Table 1 shows the physical properties of coal A and coal B. Hereinafter, when coal A and coal B are collectively described, they may be simply referred to as coal.

[0111] [Table 1]

[0112] In Table 1, Proximate analysis indicates the results of proximate analysis (JIS M 8812), and Ultimate analysis indicates the results of elemental analysis (JIS M 8819). In Proximate analysis, MOIST means moisture, and is expressed as a percentage of weight based on arrival (wt%ar). Ash and VM mean ash and volatile matter, respectively, and their values ​​are expressed as percentage of weight based on dry weight (wt%db). In Ultimate analysis, C, N, H, S, and Odiff indicate the contents of carbon, nitrogen, hydrogen, sulfur, and oxygen, in that order, as percentages of weight based on anhydrous and ashless elemental composition (wt%daf). H / C and O / C are the elemental ratios of hydrogen to carbon and oxygen to carbon, respectively. The fluidity test shows the results of a test performed in accordance with the coal fluidity test method using the Gieseler plastometer method specified in JIS M 8801.

[0113] The coal was pulverized in a cutter mill in the same manner as the semi-carbide, to obtain coal powder with a particle size of 100 μm or less.

[0114] Next, the semi-carbide powder and the coal powder were mixed so that the mixing ratios by mass were 25:75, 50:50, and 75:25, and the mixture was manually mixed in a mortar using a spatula to obtain a mixed powder. The mixed powder was molded to obtain a molded product, and the molded product was further carbonized to produce the coke of Example 2. During molding, the molding temperature was 200°C and the molding pressure was 128 MPa. The carbonization temperature was 1000°C. The molding and carbonization were performed in the same manner as in Example 1.

[0115] 11 to 16 are graphs showing the relationship between the strength of the coke in Example 2 and the blending ratio of the semi-carbide powder and the coal powder. FIG. 11 to FIG. 13 show the case where coal A is used and the semi-carbide mixed with coal A has a semi-carbonization temperature of 250°C, 275°C, and 300°C (the series names TC250-CA, TC275-CA, and TC300-CA are shown in this order). FIG. 14 to FIG. 16 show the case where coal B is used and the semi-carbonization temperature of the semi-carbide mixed with coal B has a semi-carbonization temperature of 250°C, 275°C, and 300°C (the series names TC250-CB, TC275-CB, and TC300-CB are shown in this order).

[0116] The horizontal axis of each graph shown in Figures 11 to 16 shows the above blending ratio converted into a volume based on each of the cokes produced only from cedar biomass and only from coal instead of the mass ratio. Specifically, the masses of the semi-carbide and coal at a given blending ratio are converted into the volume of the coke portion derived from the semi-carbide and the volume of the coke portion derived from the coal, and the volume of the coke portion derived from the semi-carbide is divided by the total volume of the coke portion and the volume of the coke portion derived from the coal, and the value is used as the "blending ratio (converted value)". In each graph, a blending ratio of zero is the strength of coke produced only from coal, and a blending ratio of 1 is the strength of coke produced only from semi-carbide.

[0117] According to the graphs shown in Figures 11 to 16, a positive or negative correlation is observed between the blending ratio and strength, and it is not possible to uniformly grasp the relationship between the blending ratio and strength. However, when the strength of coke prepared from coal alone is relatively high, the strength of coke produced using the mixed powder also tends to be high. The strength of each coke is high, exceeding 3 MPa regardless of the blending ratio.

[0118] With the exception of the coke made when the semi-carbonized material mixed with coal A was semi-carbonized at 250°C (TC250-CB, see Figure 14), the strength of the other cokes exceeds 5 MPa regardless of the blending ratio. Even in the case of the coke made when the semi-carbonized material mixed with coal A was semi-carbonized at 250°C (TC250-CB, see Figure 14), the strength of the coke exceeds 5 MPa when the blending ratio percentage of the semi-carbonized material exceeds 50 wt% on a mass basis.

[0119] Example 3 The same cedar biomass as in Examples 1 and 2 was used, turned into semi-carbonized material, and further mixed with the same coal A as in Example 2 to produce coke in Example 3. In Example 2, semi-carbonized material powder and coal powder were mixed to obtain a mixed powder, and then coke was produced. However, in Example 3, a mixture of semi-carbonized material and coal A was obtained, and this was crushed (co-crushed) to obtain a mixed powder and produce coke, which is different from Example 2. In the following explanation, explanations of parts similar to the conditions in Examples 1 and 2 may be omitted.

[0120] Semi-carbonized materials were obtained by semi-carbonization treatment at temperatures of 250°C, 275°C, and 300°C, and were mixed with coal A to obtain mixtures. The blending ratios of the mixtures, in terms of mass ratio of semi-carbonized material to coal A, were 25:75, 50:50, and 75:25.

[0121] Next, the mixture was pulverized to obtain a mixed powder. The mixture was pulverized in a cutter mill for 1 minute in the same manner as in the pulverization of the semi-carbide in Example 1, and the pulverized product was then subjected to a ball mill for 10 hours to obtain a mixed powder with a particle size of 40 μm or less.

[0122] The crushing of the mixture is so-called co-crushing, in which the semi-carbide and coal A are crushed at the same time. In co-crushing, the mixing uniformity of the mixed powder is naturally improved due to the stirring phenomenon caused by the crushing process. This makes it unnecessary to perform a mixing process of the mixed powder as in Example 2. The mixing of the semi-carbide and coal A before crushing the mixture can be very simple.

[0123] Next, a briquette was obtained using the mixed powder, and the briquette was further carbonized to obtain coke of Example 3. During the briquetting, the briquetting temperature was 200° C. and the briquetting pressure was 128 MPa. The carbonization temperature was 1000° C. The briquetting and carbonization were performed in the same manner as in Examples 1 and 2.

[0124] 17 to 19 show graphs illustrating the relationship between the strength and blending ratio of the coke of Example 3. The horizontal axis of each graph shows "blend ratio (converted value)" as in the case of Figs. 11 to 16 of Example 2. Figs. 17 to 19 show cases where coal A is used and the semi-carbonized material mixed with coal A is subjected to semi-carbonization treatment at temperatures of 250°C, 275°C, and 300°C, respectively (the series names are T250-CA, T275-CA, and T300-CA, respectively, in this order).

[0125] As shown in the graphs of Figs. 17 to 19, the coke of Example 3 produced by co-pulverizing the semicarbide and coal exhibits a high strength that is stable and exceeds 20 MPa regardless of the blending ratio.

[0126] In comparison with the coke of Example 2, the coke of Example 3 exhibits higher strength than the coke of Example 2, regardless of the blending ratio. The coke of Example 3, both the coke derived from coal only (blending ratio zero) and the coke derived from biomass only (blending ratio 1), have higher strength than the coke of the same blending ratio in Example 2. This result shows that the finer the particle size of the mixed powder during molding (100 μ or less in Example 2, and 40 μ or less in Example 3), the higher the coke strength.

[0127] As shown in Examples 1 to 3, the coke according to the present embodiment is a biomass-derived coke, but has high strength enough to be usable in a conventional blast furnace process. According to the coke manufacturing method according to the present embodiment, it is possible to manufacture such high-strength coke. The coke manufacturing method according to the present embodiment does not require a complicated manufacturing process or additional raw materials such as a binder to increase strength in order to manufacture such high-strength coke, and therefore can simultaneously realize low costs.

[0128] In this manner, it is possible to provide a method for producing biomass-derived coke that has sufficient strength for use in conventional blast furnace processes and is low cost.

[0129] In addition, the configurations disclosed in the above embodiments (including other embodiments, the same applies below) can be applied in combination with configurations disclosed in other embodiments, provided no contradiction arises. Furthermore, the embodiments disclosed in this specification are illustrative, and the embodiments of the present invention are not limited thereto, and can be appropriately modified within the scope that does not deviate from the purpose of the present invention. [Industrial Applicability]

[0130] The present invention is applicable to a method for producing coke.

Claims

1. a semi-carbonization step of heating woody biomass to 220° C. or higher and 330° C. or lower in an atmosphere where oxygen supply is blocked to obtain a semi-carbonized material; a mixing step of mixing the torrefied material and coal to obtain a mixture; A grinding step of grinding the mixture to a particle size of 300 μm or less to obtain a mixed powder; a molding step of heating the mixed powder to a temperature in the range of 125° C. to 300° C. and pressurizing the mixed powder to a pressure of 100 MPa to 300 MPa to obtain a molded product; and a carbonization step of converting the briquettes into coke by carbonization.

2. The method for producing coke according to claim 1 , wherein in the pulverizing step, the mixture is pulverized to a particle size of 100 μm or less to obtain the mixed powder.

3. a semi-carbonization step of heating woody biomass to 220° C. or higher and 330° C. or lower in an atmosphere where oxygen supply is blocked to obtain a semi-carbonized material; a semi-carbide crushing step of crushing the semi-carbide to a particle size of 300 μm or less to obtain semi-carbide powder; a powder mixing step of mixing the semi-carbide powder with coal powder having a particle size of 300 μm or less to obtain a mixed powder; a molding step of heating the mixed powder to a temperature in the range of 125° C. to 300° C. and pressurizing the mixed powder to a pressure of 100 MPa to 300 MPa to obtain a molded product; and a carbonization step of converting the briquettes into coke by carbonization.

4. The method for producing coke according to claim 3 , wherein in the powder mixing step, a blending ratio of the semi-carbide powder in the mixed powder is set to 50 wt % or more.

5. In the semi-carbide crushing step, the semi-carbide is crushed to a particle size of 100 μm or less to obtain the semi-carbide powder, The method for producing coke according to claim 3, wherein in the powder mixing step, the semi-carbide powder and the coal powder having a particle size of 100 μm or less are mixed to obtain the mixed powder.

6. a semi-carbonization step of heating woody biomass to 220° C. or higher and 330° C. or lower in an atmosphere where oxygen supply is blocked to obtain a semi-carbonized material; a semi-carbide crushing step of crushing the semi-carbide to a particle size of 300 μm or less to obtain semi-carbide powder; a molding step of heating the semi-carbide powder to a temperature in the range of 125° C. to 300° C. and pressurizing the semi-carbide powder to a pressure of 100 MPa to 300 MPa to obtain a molded product; and a carbonization step of converting the briquettes into coke by carbonization.

7. The method for producing coke according to claim 6, wherein in the semi-carbide crushing step, the semi-carbide powder is obtained by crushing the semi-carbide to a particle size of 100 μm or less.

8. The method for producing coke according to any one of claims 1 to 7, wherein in the semi-carbonization step, the woody biomass is heated to 250°C or higher and 300°C or lower to obtain the semi-carbonized material.

9. The method for producing coke according to claim 6 or 7, wherein in the carbonization step, the molded product is carbonized at a carbonization temperature of 500° C. or more and 900° C. or less to convert it into coke.

Citation Information

Patent Citations

  • Method for producing coke

    JP2004307683A

  • Method for producing coke by using woody material-based biomass

    JP2004359898A

  • Method for producing coke for blast furnace using wood-based biomass

    JP2005272569A

  • Method for operating blast furnace using woody biomass as raw material, and coke production method

    JP2012017528A

  • Composite solid fuel and method for manufacturing composite solid fuel

    JP2021176938A